If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 103 + x Solving 2x = 103 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x = 103 + x + -1x Combine like terms: 2x + -1x = 1x 1x = 103 + x + -1x Combine like terms: x + -1x = 0 1x = 103 + 0 1x = 103 Divide each side by '1'. x = 103 Simplifying x = 103
| -2(4x-5)=38 | | 10=25+.5x | | 11=5(n-9) | | 6(9x+18)=60 | | 3/4m=3/7 | | 6(2y+5)=78 | | x/3-19=5 | | -4+5x=87 | | 4p-3=2p+5 | | 5(18+x)+10(4x)+25x=1420 | | 75-5n=100 | | 9x-4x+5=x-5+10 | | f(2)=-3x+9 | | 4(2-4r)=72 | | x-5.1=-7.6 | | -3(2x+1)-(x-3)=-2(x-1)+6x-3(2-x) | | 48-8x=36 | | 1/8(8t-6)=t+6/16 | | 22-(x+9)=6x-8 | | 8/5-7/4y=-5/3 | | 88=16-4a | | 3x^2=3-7x | | 5x-6-7x=x+6+x | | 8/9=-1/3w-7/6 | | 9/7-9/2w=-9/5 | | 56+x=10 | | 3w-6=426 | | m^2-4m+3= | | 6+28/4+3*4 | | -3X+7y=-18 | | 6+28/4+3x4 | | 3x-6+13x-6=180 |